Educational Curriculum Policy in the Era of President Joko Widodo and Its Implications for Islamic Education - Tajurrahman, Aulia Azhari; Rohiman, Iman; Rosita, Ita (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2023)
This study investigates the education curriculum policies in Indonesia during the presidency of Joko Widodo and their impact on Islamic education. The primary objective of this research is to examine the ramifications of alterations in educational curriculum policies during President Joko Widodo's tenure, specifically focusing on the 2013 Curriculum and Merdeka Curriculum for Islamic education. This study employs a qualitative methodology, utilizing library research methods and document analysis. Information is gathered from diverse sources including books, journals, government reports, and other authoritative texts. The research findings indicate that the 2013 Curriculum in Indonesia has a significant impact on Islamic education by incorporating a scientific methodology, integrating Islamic principles, and providing flexibility in the traditional curriculum. Meanwhile, Merdeka Curriculum fosters adaptable and pertinent education, granting schools and instructors autonomy, as well as enabling innovative evaluation methods. Implementation obstacles encompass issues related to infrastructure, teacher training, and comprehension of the curriculum, all aimed at enhancing the standard of education, particularly Islamic education.